Pathophysiology of post-gastrectomy hypoglycaemia. Issue 5678 (1st November 1969) - Holdsworth, C. Derek; Turner, D.; McIntyre, Neil
Abstract : The blood glucose and plasma insulin response to oral glucose and slow intravenous infusion of glucose was determined in seven patients who had undergone partial gastrectomy or gastroenterostomy. Similar studies were conducted in normal subjects; in these experiments oral glucose administration was replaced by infusion of glucose direct into the jejunum in order to simulate the rapid gastric emptying which occurs after gastric surgery. Peak insulin levels were much higher after oral or intrajejunal glucose, though peak blood glucose levels were higher after intravenous glucose. Despite the high insulin levels occurring with oral administration the late fall in blood glucose below fasting levels was not significantly greater after oral or intrajejunal glucose than after intravenous administration of the sugar. This does not support the concept that hyperinsulinaemia alone is responsible for reactive hypoglycaemia.